PRODUKSI DAN FRAKSINASI ASAP CAIR DARI LIMBAH TONGKOL JAGUNG UNTUK PENGHAMBATAN PEROKSIDASI LIPIDA IKAN LAYANG (Decapterus russelli) - Mongan, Jemsi; Suryanto, Edi; Rumengan, Inneke (Sam Ratulangi University, 2011)
ABSTRACTMongan et al., 2011. Production and fractionation of liquid smoke from corn cob to inhibit lipid peroxidation oflaying fish (Decapterus russelli).Corncob is a cellulose material and can be made to liquid smoke by pyrolysis. Liquid smoke from pyrolysis canbe purified using adsorbent. Chitin is an adsorbent produced by crustacea shell. Liquid smoke purified by chitincan act as antimicroba and antioxidant. Layang fish is very abundantly in Gorontalo Province, so preservativetechniques were needed to prevent lipids peroxidation in fish. The aims of this research was to determineantioxidative activity of liquid smoke from corncop to prevent lipids peroxidation on layang fish.This research using laboratory experiment methods to analyze total phenolic content, free radical scavengingactivity, total antioxidant and lipids peroxidation on layang fish by spectrophotometer UV-vis. This researchusing complete random design (rancangan acak lengkap, RAL), thus obtained data were analyzed usingstatistic. Significant difference between groups were analyzed using ANOVA with p<0,05. If there is significantdifference between groups, data were analyzed using Duncan’s multiple range test (DMRT).The results showed that liquid smoke can be produced using corncop by pyrolysis is 31,7 %. Fractioned liquidsmoke using chitin obtained 4 fractions were fraction I, II, III and IV. Liquid smoke and fractioned liquid smokecontain total phenolic content are 280, 273, 280, 286 and 301 mg/kg gallic acid, respectively. Free radicalscavenging activity from liquid smoke and fractioned liquid smoke are 87,39, 86,08, 89,29, 89,90 and 93,73%,respectively. Although, total antioxidant from liquid smoke and fractioned liquid smoke are 59, 35, 51,32, 51,57,52,74 and 53,58 ppm, respectively. Fraction IV of liquid smoke fractioned with chitin was used in antioxidativeactivity of laying fish test. Fraction IV with concentration 25% can inhibit lipid peroxidation on fresh layang fishby 19 mikromolar for two days. Although layang fish without liquid smoke shows high lipid peroxidation by 24,96mikromolar. Fraction IV with concentration 25% can inhibit lipid peroxidation on layang fish by 18,28 mikromolarfor two days. Antioxidative activity from liquid smoke caused by it phenolics compound that act as antioxidant.As conclusions of this research, liquid smoke can be produced from corncob and fractioned with chitin. Liquidsmoke contain phenolics and act as antioxidant. Liquid smoke can inhibit lipids peroxidation in layang fish. Thisresearch suggested that liquid smoke can be used to inhibit lipid peroxidation on layang fish..Keywords : liquid smoke, corn cob, peroxidation, layang fish